Alarmin human α defensin HNP1 activates plasmacytoid dendritic cells by triggering NF-κB and IRF1 signaling pathways. (July 2016) - Wang, Fang; Qiao, Linan; Lv, Xing; Trivett, Anna; Yang, Rui; Oppenheim, Joost J.; Yang, De; Zhang, Ning
Highlights: HNP-1 induced pDC activation in vitro . HNP-1 triggered NF-κB and IRF-1 signaling. NF-κB and IRF-1 played important roles in HNP-1-induced pDC activation. HNP-1 stimulated pDC activation in SCID mice. Abstract: Human neutrophil peptide 1 (HNP1), a predominant α defensin in the azurophilic granules of human neutrophils, is an alarmin capable of inducing the migration and maturation of human myeloid/conventional dendritic cells. However, it is not determined whether it can activate plasmacytoid dendritic cells (pDCs). Herein, we found that both human pDCs and CAL-1 cells, a pDC-like cell line, produced IFNα upon treatment with HNP1. Additionally, HNP1 could promote CpG ODN-induced pDC production of proinflammatory cytokines including IFNα. HNP1 triggered activation of NF-κB and nuclear translocation of interferon regulatory factor 1 (IRF1) in CAL-1 cells. HNP1 upregulation of cytokine expression in pDCs was inhibited by blockade of NF-κB activation or knockdown of IRF1, demonstrating the importance of these two signaling events in HNP1-induced pDC activation. Using a human pDC-nude mouse model, HNP1 was shown to induce IFNα production by human pDCs in vivo . Thus, HNP1 can activate human pDCs using NF-κB and IRF signaling pathways, and HNP-induced IFN production may participate in the inflammatory pathogenesis in certain authoimmune diseases such as rheumatoid arthritis.